2013
DOI: 10.1111/maec.12077
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of bacteria with diatoms: influence on natural marine biofilms

Abstract: Interactions between microfouling components influence the biofilm community and the cascading events, thus playing an important role in the biofouling process. Bacteria and diatoms are among the dominant forms reported in biofilms. Experiments were carried out with natural marine biofilms from a tropical monsoon-influenced environment to evaluate the interactions between bacteria and diatoms through application of antibiotics (streptomycin and chloramphenicol). Overall, chloramphenicol inhibited diatom commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Samples grown in the low‐nutrient media cover a larger area faster, similar to the evolution of fast growth when nutrients are reduced or only available during short periods of time (Ketola et al ). Increased biofilm formation in response to competition for nutrients (Oliveira et al ) at higher temperatures is in accordance with short‐term studies carried out on bacteria and mixed algal‐bacteria biofilm assemblages (Villanueva et al ; Mosier et al ) and observations that followed diatom biofilms throughout monsoon seasons (Khandeparker et al ). Mild warming of 4°C, which is within the range of predicted IPCC scenarios (RCP 4.5, IPCC 2014), increases biofilm formation by close to two‐fold in nutrient replete as well as low‐nutrient conditions compared to biofilms evolving under control conditions.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Samples grown in the low‐nutrient media cover a larger area faster, similar to the evolution of fast growth when nutrients are reduced or only available during short periods of time (Ketola et al ). Increased biofilm formation in response to competition for nutrients (Oliveira et al ) at higher temperatures is in accordance with short‐term studies carried out on bacteria and mixed algal‐bacteria biofilm assemblages (Villanueva et al ; Mosier et al ) and observations that followed diatom biofilms throughout monsoon seasons (Khandeparker et al ). Mild warming of 4°C, which is within the range of predicted IPCC scenarios (RCP 4.5, IPCC 2014), increases biofilm formation by close to two‐fold in nutrient replete as well as low‐nutrient conditions compared to biofilms evolving under control conditions.…”
Section: Discussionsupporting
confidence: 85%
“…Diatoms and their associated bacteria form biofilms on surfaces of sinking or floating debris and on benthic structures in shallow, coastal areas (Amin et al ; Doiron et al ; Khandeparker et al ; Windler et al ). Planktonic diatoms may also aggregate through increased production of transparent exopolymer particles (TEPs; see de Brouwer et al ; Berman et al ; Windler et al ).…”
mentioning
confidence: 99%
“…All these results showed that AHLs produced by bacteria noticeably increased the diatom-biofilm biomass and EPS production. It was reported that the interaction between diatoms and bacteria in biofilm might be regulated by a complex network of chemical factors including EPS and other substances (Khandeparker et al, 2014). For example, bacteria influenced the diatom community structure by antibiotic-mediated interactions (D'Costa and Anil, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In the field, barnacles are covered with epibiotic biofilm, and bacteria in the biofilm matrix have been reported to play an important role in barnacle settlement (Khandeparker et al . , , ; Khandeparker & Kumar ; Bacchetti De Gregoris et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…In the field, barnacles are covered with epibiotic biofilm, and bacteria in the biofilm matrix have been reported to play an important role in barnacle settlement (Khandeparker et al 2003(Khandeparker et al , 2006(Khandeparker et al , 2014Khandeparker & Kumar 2011;Bacchetti De Gregoris et al 2012). In a pilot study, Khandeparker et al (2003) reported that exopolymers from the shell-associated bacteria can induce barnacle larval settlement and another study proved the uniqueness of these bacteria to the barnacle shell, which helps the cyprid to recognize parentally associated biofilms (Bacchetti De Gregoris et al 2012).…”
Section: Introductionmentioning
confidence: 99%